Adwa' al bayan fii idah al Qur'an bi al Qur'an - Muhammad al Amin Ibn Muhammad al Mukhtar al Jakaniy al Shanqitiy (Dar al Fikr, 1995)
ws.jl.1-3,5,8-9.c.1-3, jl.4,6-7.c.1-2/stoc1, jil.1-3,5,8-9=c.1-3 ; jil.4,7=c.1-2 ; jil.7,c.1